Modeling, design and control of a modified flyback converter with ability of right-half-plane zero alleviation in continuous conduction mode - Alireza Goudarzian; Adel Khosravi; Heidar Ali Raeisi (Engineering Science and Technology, an International Journal, 2022)
For fuel cell applications, a module-integrated dc/dc converter with the isolation capability is an important part of a power distribution system. It increases the low input voltage of a fuel cell to a desire high voltage and behaves as an interface connection circuit. There are several isolated dc/dc converters for connecting a fuel cell module to a power load. Among them, Flyback converter is a good candidate and widely used for fuel cell applications, due to its simple structure; however, the internal dynamics of a Flyback converter involves a right-half-plane zero (RHPZ), resulting in its performance degradation. Hence, the open-loop gain margin of a Flyback converter is small and its open-loop phase margin is negative, leading to difficulties for development of a voltage-mode controller. The major objective of the article is to address the aforementioned problems and present a new approach for eliminating them. To this end, a modified Flyback topology with ability of the RHPZ elimination is suggested and analyzed in this study and also, the superior performance of the modified converter is demonstrated in comparison with a classical Flyback converter. Then, the dynamical model of the designed circuit is derived using the averaging method and the design rules are determined. In addition, the theoretical model of the developed converter is validated via simulations and experiments. To keep the load voltage of this topology at a fixed value and, show its good performance for industrial applications, the type-II/III controllers are designed and the obtained simulated and practical results are introduced.